Rural industrialisation : India's experience and programme for developing countries - Jain, P.O. (New Delhi : Commercial Publications Bureau, 1975)
The author shows how, over successive plans, the programmes for establishment of rural industries- whether in propitious growth centres or difficult backward areas- have shed the character of isolated experiments and come to be regarded as parts of a composite endeavour. Many factors, including market and raw material, skill and capital, inputs and infrastructure- pertaining to the particular area, must be taken note of and given due place while imparting shape to that endeavour. Jain analyses these factors with reference to at least five different patterns which he discerns in the Indian situation.
Includes index.
Includes bibliographical references: p. 299-311.
lje 09/04/2018
Loans
Keywords: Industrialisation; Rural industrialisation; Rural development; India